Design of a Test Rig for the Characterization of Thermal Fatigue and Soldering Resistance of the Surfaces of Tool Steels for High‐Pressure Die‐Casting Dies. Issue 5 (16th December 2019) - Gobber, Federico Simone; Pisa, Andrea Giuseppe; Ugues, Daniele; Rosso, Mario
Abstract : The conceptualization and development of a test rig able to reproduce thermal stresses and contact with molten aluminum alloy, typical of high‐pressure die‐casting dies, are described. During the test, a hot‐work tool steel sample is cyclically heated by contact with molten aluminum alloy (AlSi11Cu2(Fe)) and then cooled by the spraying of a water‐diluted silicone‐based lubricant. A finite element method (FEM) simulation is setup to determine the temperature at different depths beneath the sample surface during thermal cycling and is experimentally validated to design the proper sample geometry aimed at reproducing the stress/strain conditions experienced by a die‐casting die insert. A tensile–compressive stress state is achievable on the surface of the sample by machining a notch with a suitable radius, which is able to produce a plastic strain comparable with the insert one. A thermally induced stress–strain fatigue loop is determined for both the sample and the component. Temperatures are monitored discontinuously by infrared (IR) thermography after heating and continuously by thermocouples placed at a reference depth of 5.5 mm. Finally, the optimized testing conditions are validated experimentally: both thermal cracking and soldering phenomena are successfully reproduced on a lab‐scale test rig. Abstract : A test rig for the environmental simulation of die‐casting die materials, developed through a coupled experimental–numerical approach, is presented. The results suggest that this test rig can be reliable in characterizing new materials for dies as in characterizing thermal properties of innovative conformally cooled dies fabricated by additive metallurgy processes.